1986
DOI: 10.1021/bi00372a029
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cytochrome b in mitochondria from yeast lacking coenzyme Q

Abstract: Mitochondria isolated from coenzyme Q deficient yeast cells had no detectable NADH:cytochrome c reductase or succinate:cytochrome c reductase but had comparable amounts of cytochromes b and c1 as wild-type mitochondria. Addition of succinate to the mutant mitochondria resulted in a slight reduction of cytochrome b; however, the subsequent addition of antimycin resulted in a biphasic reduction of cytochrome b, leading to reduction of 68% of the total dithionite-reducible cytochrome b. No "red" shift in the abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Like Ernster et al (43) before us, we found in antimycin-treated, Q-extracted bovine SMP that succinate addition results in a slow reduction of cytochrome b, which could be considered due to the presence in these particles of a residual amount of Q. However, similar results have been reported by Clejan and Beattie (25) with Q-deficient yeast mitochondria and have been found by ourselves with Q-deficient yeast SMP, except that in our experiments the extent of succinate-induced b reduction was less. It is possible that in the absence of Q the low potential b 560 of complex II can slowly reduce the b of complex III.…”
Section: Reduction Of B H By Ascorbateϩtmpd In Ubiquinone-extracted Bsupporting
confidence: 90%
See 2 more Smart Citations
“…Like Ernster et al (43) before us, we found in antimycin-treated, Q-extracted bovine SMP that succinate addition results in a slow reduction of cytochrome b, which could be considered due to the presence in these particles of a residual amount of Q. However, similar results have been reported by Clejan and Beattie (25) with Q-deficient yeast mitochondria and have been found by ourselves with Q-deficient yeast SMP, except that in our experiments the extent of succinate-induced b reduction was less. It is possible that in the absence of Q the low potential b 560 of complex II can slowly reduce the b of complex III.…”
Section: Reduction Of B H By Ascorbateϩtmpd In Ubiquinone-extracted Bsupporting
confidence: 90%
“…Preparation of SMP from Wild-type and Ubiquinone-deficient Yeast (Saccharomyces cerevisiae)-The wild-type yeast strain (D273-10B) and the ubiquinone-deficient strain E3-24 (24) were generous gifts of Dr. Diana Beattie, West Virginia University, Morgantown, WV. Each strain was spread on an agar plate, and the cells were grown from a single colony in a medium containing galactose as carbon source as described in the literature (25). Mitochondria were prepared in a medium containing 0.6 M sorbitol and 10 mM potassium phosphate, pH 7.4, after treatment of the cells with zymolyase according to Daum et al (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation